Evaluation of First-line and High-altitude Alpine Therapies for Patients with Immune Thrombocytopenia (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Acquired thrombocytopenia is a condition that causes immune thrombocytopenia (ITP) and ischaracterized by a platelet count of 100 × 109/l. The main challenges faced by Kyrgyz patients with ITP includethe lack of clearly defined therapeutic regimens, high rate of complications associated with glucocorticoid use,unpredictability in treatment outcomes, and limited access to novel drugs. We aimed to evaluate the safety andefficacy of initial and supplementary treatments for individuals with ITP. Methods: Between 2015 and 2022,data from two sites in Kyrgyzstan, one in the country’s south and the other in the Republic, were retrospectivelyanalyzed for 172 patients who met the inclusion criteria. The initial treatment regimen followed the currentstandards, consisting of several injection courses with a dose ranging from 0.4 to 1 g/kg over one to five doses. Inaddition, dexamethasone was delivered at a dosage of 40 mg orally or intravenously every day for 4 days, alongwith prednisone at a daily dosage of 1–40 mg for up to 4 weeks. Results: Only 22.4% of patients showed clinicaland hematological improvement with prednisone treatment, and no partial or complete remission was observed.Of 91 patients, 57 (62.6%) experienced adverse events due to prednisone. The most common adverse eventswere hyperglycemia and metabolism (34.1%), followed by mental disorders (27.5%), sleeplessness (23.1%),hypertension (15.4%), and skin disorders (12.1%). Conclusion: In 45.4–77.6% of cases, conservative treatmentapproaches can effectively treat adult ITP patients. Current treatments include prednisone, dexamethasone, andthe combined use of intravenous immunoglobulin, rituximab, and azathioprine.